Ensino da língua portuguesa na perspectiva da inclusão do aluno cego no nível fundamental - Cunha, Marleide dos Santos (2015)
The general purpose of this research was to analyze the Portuguese language teaching in a literacy class and in the 8th year of an elementary school, having, as empirical field, an institution that provides Specialized Educational Assistance for visually impaired people in Sergipe and a regular classroom with blind students included, in a public school in Aracaju. Thus, in order to fill a lack of research about Portuguese language teaching of to people with blindness in the capital of Sergipe, we used the qualitative case study methodology. Data collection instruments were semi-structured interviews, unsystematic and systematic observations, literature review and document analysis. The results allow us to say that Portuguese language teaching in the observed classes is disconnected from the social uses of reading and writing. Resources of Assistive Technology (AT) in the two classes are barely explored. Even considering that, in undergraduate curricula of Letters/Portuguese and Pedagogy courses, there are subjects that address the basic contents legally required to train teachers in the perspective of inclusive education, the educators still consider themselves unprepared to teach students with disabilities. It shows a total dependence on the help that students receive from the Specialized Educational Assistance, since the experts teachers of this service are usually trained in content updates courses about inclusion. On the other hand, regular Portuguese teachers and the ones of the Specialized Educational Assistance are not used to work cooperatively. Finally, this study points out the reality found and strengthens the hope we are advancing in the search for teaching strategies that address the needs of blind students in a school that aims at the effectiveness of inclusive education.